Problematizing the teaching of chemistry through the reading of packages/labels: a proposal for the second year of high school - Soethe, Antuir Alves (2018)
This article presents an experience report, carried out during the Supervised Internship in the degree in chemistry and aimed to provide the teaching of the content of solutions through the reading and interpretation of packaging/labels of cleaning products, relating the terms, scientific concepts presented in the information contained in this material with the chemical concepts approached in the classroom. The paths covered involved four steps: application of a diagnostic questionnaire; presentation of concepts on the study of solutions; proposition of the study and interpretation of information on packages/labels according to the methodology of Machado and Mortimer (2003); the production of videos and the application of the final questionnaire to analyze the students' learning. From the analyzes carried out, it is possible to verify that the students expanded their perspectives on the interpretation of packaging/labels and realized the importance of the habit of reading this information on the products. In the production of the videos, the students expanded their interpretations about the different types of solution, the different ways of calculating the concentration of the solutions, the concept of concentration and dilution. The development of this didactic methodology provoked concerns, pointing out other paths, different from what is commonly observed in schools: contextualization promoted new perspectives for the teaching of chemistry.